The Influence of Company Size, Fixed Asset Intensity and Sales Growth on Tax Avoidance - Faza Shafiraanjali; Nur Asmilia (Business Finence Analyst Co.,, 2024)
This study aims to obtain empirical evidence of the simultaneous influence of company size, fixed asset intensity, and sales growth on tax avoidance. Obtain empirical evidence of the influence of company size on tax avoidance. Obtain empirical evidence of the influence of fixed asset intensity on tax avoidance. Obtain empirical evidence of the influence of sales growth on tax avoidance. The population in this study is Consumer Non-Cyclicals companies in the Food and Beverage subsector listed on the Indonesia Stock Exchange (IDX) in 2018-2022, namely 94 companies. Sampling was carried out using the purposive sampling method and a sample of 18 companies was obtained. So that the number of data processed with an observation period of 5 years is 90 data. This type of research is quantitative and uses secondary data. Data collection techniques are carried out by documentation and literature studies. The data analysis techniques used were descriptive statistical analysis, classical assumption test, panel data regression analysis and hypothesis test using the help of Eviews 13. The results of the study showed company Size, Fixed Asset Intensity simultaneously had a significant effect on tax avoidance. The size of the company has a negative effect on tax avoidance. Fixed Asset Intensity has a significant effect on tax avoidance. 4) Sales Growth has no effect on tax avoidance.